A low-cost and high-strength Ti-Al-Fe-based cast titanium alloy for structural applications. (December 2018) - Liang, Zhi; Miao, Jiashi; Brown, Tyson; Sachdev, Anil K.; Williams, James C.; Luo, Alan A.
Abstract: A cost-effective α-β titanium casting alloy, Ti-6Al-5Fe-0.05B-0.05C, 1 has been designed using Calculation of Phase Diagrams (CALPHAD) method and the workhorse alloy Ti-6Al-4 V as a baseline. The substitution of iron for vanadium significantly reduces the raw material cost and improves the castability compared to the Ti-6Al-4 V alloy. The very fine α phase in the microstructure of the new alloy, likely due to Fe partitioning, provides exceptionally high strength (1023 MPa yield strength and 1136 MPa ultimate tensile strength) and reasonable ductility (3.71% elongation) for structural applications. Graphical abstract: ASTM E8 tensile test result with microstructures of as-cast Ti-6Al-5Fe-0.05B-0.05C. Unlabelled Image